1994
DOI: 10.1055/s-0038-1634989
|View full text |Cite
|
Sign up to set email alerts
|

The Value to the Anaesthetist of Monitoring Cerebral Activity

Abstract: Abstract:The administration rate of general anaesthetic drugs is at present guided by clinical experience, and indirect indicators such as haemodynamic parameters. In the presence of muscle relaxants most of the clinical signs of inadequate anaesthesia are lost and accidental awareness may occur. A number of monitoring modalities, primarily based on analysis of the electroencephalogram (EEG), have been proposed for measurement of the anaesthetic depth. Moreover intraoperative cerebral monitoring may also provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Langford and Thomsen concluded that no single measure derived from electroencephalogram, sensory evoked potentials or heart rate variability can alone meet all of the requirements for intraoperative monitoring of cerebral functions [19]. Our previous studies support this, showing the correlation between EEG transients and heart rate [20], as well as the reversed phase relationship of RSA during positive pressure ventilation [15].…”
Section: Discussionsupporting
confidence: 71%
“…Langford and Thomsen concluded that no single measure derived from electroencephalogram, sensory evoked potentials or heart rate variability can alone meet all of the requirements for intraoperative monitoring of cerebral functions [19]. Our previous studies support this, showing the correlation between EEG transients and heart rate [20], as well as the reversed phase relationship of RSA during positive pressure ventilation [15].…”
Section: Discussionsupporting
confidence: 71%
“…The contribution by Kawahara et al: Interactions between respiratory, cardiac and stepping rhythms in decerebrate cats: functional hierarchical structures of biological oscillators [4] is in many aspects very similar to the previous one. The authors show care in well defining the problem, the biological signals under study and the signal processing methods they have applied, mainly the coherence function to estimate the coupling strength between respiratory, cardiac and stepping rhythms during fictive locomotion in cats.…”
Section: Synopsis and Editorial Commentarymentioning
confidence: 60%
“…The work presented in the two previous papers has been achieved thanks to a close collaboration between physiologists and engineers. There is evidence of another fruitful collaboration between physicians and scientists in the paper from Langford and Thomsen [4]. They provide an excellent, lucid discussion on "The value to the anesthetist of monitoring cerebral activity".…”
Section: Synopsis and Editorial Commentarymentioning
confidence: 99%
See 1 more Smart Citation